(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article Input a word of English political views educator Henry St. Dzhona Bolingbroka. British statesman and philosopher G. Bolingbrok was the brightest representative of the early English Enlightenment, the spokesman of ideas of empiricism and sensationalism. In 1738 G. Bolingbrok some time was an adviser to Frederick, Prince of Wales, who was in opposition to his own father George II; I wrote (On the Idea of a Patriot King) for his essay, «The idea of the King-patriots.» Bolingbroke lost faith and interest in the parliamentary opposition Tories decided to write down his political credo. It is expressed in his major works devoted to the problem of power – in the «Idea of King-Patriot» («The Idea of a Patriot King», published in 1749). Since we are talking about the future, and «possible» in modern England Bolingbroke – we purest political utopia. Since we are talking about the analysis of the nature of power itself – we see an interesting monument of political thought in the first half of XVІІІ century. Key words: Enlightenment, King Patriot, the Tory opposition, parliament, reform absolutism, humanism.